Cellulose‐Based Electrolytes for Advanced Lithium‐Ion Batteries: Recent Advances and Future Perspectives. Issue 8 (21st June 2022) - Zhang, Lei; Gao, Haiqi; Jin, Gan; Liu, Shuo; Wu, Jiawei; Wu, Hao; Yang, Yuqing; Wang, Qian; Wang, Shi
Abstract: In the coming decades, it is urgent to find a way to power the future while keeping a clean environment and strong economic growth. Thus, it is expected to transition from using fossil fuels to renewable energy. Materials based on cellulose are abundant, low cost, sustainable, possess a high surface area, good thermal stability, biocompatibility, mechanical flexibility, and inherit unique layered fiber structure from cellulose, which can act as an ideal electrolyte matrix for sustainable and high energy density lithium‐ion batteries (LIBs). In this review, we focus on energy storage application of different forms of cellulose‐based electrolytes in LIBs. Specifically, we summarize the recent advances of cellulose‐based gel and solid‐state electrolytes, focusing on the gel electrolytes based on different types of plasticizers (cellulose‐based electrolytes for flexible LIBs also are introduced). Finally, several perspectives related to the cellulose‐based‐electrolytes for LIBs are proposed based on recent progress and our own evaluation. Abstract : A systematic summary of cellulose‐based electrolytes for lithium‐ion batteries, including gel electrolytes and solid‐state electrolytes, with emphasis on gel electrolytes, is provided. Furthermore, their applications in flexible lithium‐ion batteries and future perspectives are presented in this review.